النكرة في سياق النفي أو ما في معناه في القراءات القرآنية العشر المتواترة: The negation in the context of the negation or its meaning in the Qur’anic readings - Abdulwahhb, Warqaa Abdulsalam (SIBAWAYH Arabic Language and Education, 2021)
إنَّ للقرآن الكريم الفضل الكبير على علوم عِدّة ، فهو يُعدّ المصدر الأول من مصادر التشريع الأصلية عند الأصوليين لإثبات الأحكام الشرعية ، كما إنَّ تعدد القراءات تُعدُّ من أهم أسباب اختلاف المعنى ، ومن هنا جاءت أهمية هذا البحث في أنه يتعلق بمصدرين مهمين من مصادر استمداد علم أصول الفقه وهما :القرآن الكريم واللغة العربية. والنكرة في سياق النفي أو ما في معناه من صيغ العموم والتي قد تدلّ على معاني مختلفة وهذا راجع إلى اختلاف القراءات القرآنية والتي هي حقّ لا تضاد فيه فهي بمنزلة الآية مع الآية ، فيجب قبولها والإيمان بها والعمل بمقتضاها. The Holy Qur’an has great merit for several sciences, it is considered the first source of the original sources of legislation for the fundamentalists to prove the legal rulings, also, the multiplicity of readings is one of the most important reasons for the difference of meaning. Hence the importance of this research in that it relates to two important sources of derivation of the science of jurisprudence: the Noble Qur’an and the Arabic language. The denial is in the context of negation or what is in its meaning of general formulas that may indicate different of meaning, and this is due to the difference in the Qur’anic readings, which are a right that does not contradict it. Keywords: The negation, Quranic Readings